Retraction: Hsa_circ_0003645 shows an oncogenic role by sponging microRNA‐1299 in hepatocellular carcinoma cells. Issue 6 (28th February 2020) - Yu, Qiuyun; Dai, Jinhua; Shu, Ming
Abstract : Retraction: "Hsa_circ_0003645 shows an oncogenic role by sponging microRNA‐1299 in hepatocellular carcinoma cells", by Qiuyun Yu, Jinhua Dai, Ming Shu, Journal of Clinical Laboratory Analysis, 2020, e23249 (https://doi.org/10.1002/jcla.23249 ). The above article, published online on 28 February 2020 in Early View in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, the journal Editor‐in‐Chief Junming Guo, and John Wiley & Sons Ltd. The retraction has been agreed because the data and figures, including figure 7A, that the authors present in the paper are flawed. The authors' original data are not available. The conclusions drawn from the data and figures are unreliable.